2020
DOI: 10.1007/s10578-019-00954-w
|View full text |Cite
|
Sign up to set email alerts
|

Experience Versus Report: Where Are Changes Seen After Exposure-Based Cognitive-Behavioral Therapy? A Randomized Controlled Group Treatment of Childhood Social Anxiety Disorder

Abstract: A considerable number of children and adolescents with social anxiety disorder (SAD) do not benefit from treatment as much as expected. However, treatment success should not be measured with social anxiety reports alone; the cognitive, behavioral, and physiological components of social stress should also be assessed. The authors examined an exposure-based SAD-specific group cognitive behavioral therapy (CBT) in a randomized controlled trial (N = 67, age 9-13 years, blind randomized allocation to treatment [CBT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 76 publications
1
26
0
Order By: Relevance
“…Previous studies have shown that CBT is indeed able to change symptoms of anxiety (Chu & Harrison, 2007 ). Most interestingly, findings from the current sample have shown a CBT induced change in social anxiety symptoms (Asbrand et al, 2020 ) and cognitions (Asbrand et al, 2019 ). However, research on effects of CBT aside from core symptoms such as anxiety or cognitions is scarce.…”
Section: Introductionmentioning
confidence: 54%
See 2 more Smart Citations
“…Previous studies have shown that CBT is indeed able to change symptoms of anxiety (Chu & Harrison, 2007 ). Most interestingly, findings from the current sample have shown a CBT induced change in social anxiety symptoms (Asbrand et al, 2020 ) and cognitions (Asbrand et al, 2019 ). However, research on effects of CBT aside from core symptoms such as anxiety or cognitions is scarce.…”
Section: Introductionmentioning
confidence: 54%
“…As the current study was part of a larger research project requiring a larger sample size of at least N = 110, all children were included to increase power. As the current study is part of a larger project of which other results have been published previously, the following method section is based on these reports (Asbrand et al, 2019 , 2020 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Treatment consisted of an exposure-based CBT treatment that was evaluated simultaneously (Asbrand, Heinrichs, Schmidtendorf, Nitschke, & Tuschen-Caffier, 2020 focus on exposure. Each session consisted of 100 min (including a 10-min break) in groups of five to seven children.…”
Section: Treatmentmentioning
confidence: 99%
“…According to the Statistical Manual of Mental Disorders, 5th edition (DSM-5) [ 5 ], a clinical diagnosis of social anxiety disorder (SAD), requires symptoms that cause significant distress and/or impairment to the individual affected [ 6 ]. The core symptom of SAD is a fear of being negatively evaluated by peers, that is often combined with difficulty functioning in social settings [ 7 ]. As such, the association between SAD and peer relationships has been examined in clinical [ 8 ], developmental [ 9 ], and social-cognitive psychological domains [ 10 ].…”
Section: Introductionmentioning
confidence: 99%